Analisis Pengaruh Kinerja Badan Penyelenggara Pendidikan terhadap Kinerja Keuangan Perguruan Tinggi Swasta dimediasi Intellectual Capital dan Good University Governance - Listiyowati Listiyowati (Jurnal Ilmiah Aset, 2017)
Financial performance in private colleges is one of the important factors for achieving quality education. The phenomenon shows that the financial performance of private universities is not good, especially in terms of liquidity (current ratio) that encourage private universities committed some offense in getting the revenue to finance any operations of the institution. The purpose of this study is to analyze and describe the performance of the organizing body of education on college financial performance through intellectual capital and good university governance. Analysis of the data used path analysis. The results show the performance of the organizing body of education, intellectual capital and good university governance have significant influence and improve the financial performance of the college directly. But the performance of the education governing body had no significant effect on the financial performance through good university governance as well as good university governance on financial performance through intellectual capital.